Answer:
3. 3(x+y)(x-y)
4. (y²+4)(y+2)(y-2)
5. 2(3x+1)(x+2)
Step-by-Step:
3. 3(x²-y²) = 3(x+y)(x-y)
4. y⁴-16 = (y²+4)(y²-4)= (y²+4)(y+2)(y-2)
5. 6x²+14x+4 = 2(3x²+7x+2) = 2(3x+1)(x+2)
PLEASE RATE!!! I hope this helps!!!
If you have any question comment below
(I have verified my answers on an online calculator)
Answer:
38
Step-by-step explanation:
9 + 10 + 2 + 6 + (9 - 2) + (10 - 6) = 38
Answer: 25
Equation:
2(7)+2(x)=64
14+2x=64
2x=64
X=25
Hope this helps :)
Answer:
y=15
x=43
(any variable can be used, I used x and y to make it easier to show)
Step-by-step explanation:
x+y=58
x-y=28
get x by its self
x=58-y
then subsitute into the other equation
(58-y)-y=28
58-2y=28
-2y=-30
y=15
sub. again
x+15=58
x=43